1999
DOI: 10.1007/s11746-999-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of fatty acid methyl esters to fatty alcohols at supercritical conditions

Abstract: Extremely rapid hydrogenation of fatty acid methyl esters (FAME) to fatty alcohols (FOH) occurs when the reaction is conducted in a substantially homogeneous supercritical phase, using propane as a solvent, over a solid catalyst. At these conditions, the limitations of hydrogen transport are eliminated. At temperatures above 240°C, complete conversion of the starting material was reached at residence times of 2 to 3 s, which is several orders of magnitude shorter than reported in the literature. Furthermore, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Typical conditions are: hydrogen pressures between 25 and 35 MPa, temperatures ranging from 250 to 350°C [8,9]. When applied in fixed-bed reactors, the throughput under such conditions is only about 0.2-0.3 m product 3 /m reactor 3 h -1 , high H 2 /substrate ratios are usually indispensable [10]. However, the use of toxic Cr and severe reaction conditions are problematic from environmental and energetic viewpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Typical conditions are: hydrogen pressures between 25 and 35 MPa, temperatures ranging from 250 to 350°C [8,9]. When applied in fixed-bed reactors, the throughput under such conditions is only about 0.2-0.3 m product 3 /m reactor 3 h -1 , high H 2 /substrate ratios are usually indispensable [10]. However, the use of toxic Cr and severe reaction conditions are problematic from environmental and energetic viewpoints.…”
Section: Introductionmentioning
confidence: 99%
“…The use of supercritical operation conditions were studied by Van den Hark et al They found that an extremely rapid hydrogenation of fatty acid methyl esters to fatty alcohols occurs when the reaction is conducted in a substantially homogeneous supercritical phase, using propane as a solvent, over a solid catalyst (chromium‐free, copper‐based catalyst, Davy Process Technology, Cleveland, England). In these conditions, the limitations of hydrogen transport are eliminated .…”
Section: Influence Of Operating Conditions On the Conversion Of Methymentioning
confidence: 99%
“…For example, millions of tons of fatty alcohols are produced annually by reducing the corresponding fatty acid esters. 1 The most commonly used reductants for this purpose are hydrides such as lithium aluminum hydride (Scheme 1a). 2 However, because hydrides are usually water sensitive (and thus require special care during use) and produce at least stoichiometric by-products, the search for alternative, green methods for ester reduction has become an important research task in academia and industry.…”
Section: Introductionmentioning
confidence: 99%